Causal pathways of intergenerational poverty transmission in selected EU countries - Papanastasiou, Stefanos; Papatheodorou, Christos (Social Cohesion and Development, 2018)
The paper investigates whether, in what way and to what extent the family of origin affects offspring’s poverty risk in selected EU countries representing different social protection systems. Employing logit models and utilizing EU-SILC data, the analysis brings to the forefront the importance of social protection for intercepting the intergenerational transmission of poverty. Denmark with the socialdemocratic welfare state is the most successful in mitigating the effect of the family of origin on offspring’s poverty risk, followed by France representing the conservative-corporatist welfare regime. Less effective οn this matter appear to be Greece and Great Britain representing the south-European and the liberal social protection system respectively.